ANALYSIS OF POSSIBILITIES OF EVAPORATIVE COOLING IN AUTONOMOUS AND COMBINED SYSTEMS - Doroshenko A.V.; Glauberman M.A. (Problems of the Regional Energetics)
It is described possibility of the use of the evaporative cooling as in autonomous version of execution, so in combined systems, for example, as the component of desiccant–evaporative coolers, where preliminary dehumidification of the air assures high efficiency of subsequent evaporative cooling and the depth of the cooling.